Polysaccharides as Battery Components - Spirk, Stefan (Biobased Polymers, 2018)
The brief gives a comprehensive overview of the polysaccharide applications  in the field of battery materials. Included is a historic overview as well as recent developments in the field including new battery types and chemistries. Written in an accessible style by academics, it is aimed at those new to the field as well as individuals who have interest in novel polysaccharide applications. Aimed at advanced undergraduates, academic and industrial researchers and professionals studying or using biobased polymers.